Sosialisasi Pemanfaatan Mesin Pencacah dalam Pengelolaan Sampah Mendukung SDGs Desa Peswaran Indah - Prayitno, Hadi; Amrul; Irsyad, Muhammad; Nafrizal; Supono (Penerbit Goodwood, 2025)
Purpose: The purpose of this community service program in Desa Pesawaran Indah is to enhance public understanding and participation in sustainable waste management by introducing the 7R principles: Rethink, Refuse, Reduce, Repurpose, Reuse, Recycle, and Rot. Methodology: The program utilized a structured socialization approach, which included developing educational materials and conducting interactive discussions with village officials and members of the Women’s Farmers Group (KWT). Each 7R principle was introduced, practical applications were explored, and local waste management challenges were addressed. Results: The program resulted in a substantial increase in participants' understanding, with comprehension levels rising from an initial 2-4 participants to 18-21 participants who fully understood key principles like